Ukrainian cinematography in the context of intercultural cooperation - Pohrebniak, Halyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article describes the production and distribution of Ukrainian films and establishes scientific guidelines that will contribute to a comprehensive analysis of Ukrainian cinema in the intercultural space. An analytical method was used to develop this topic, which is necessary for studying the art history and cultural aspect of the problem. In addition, the author used the methods of systematization and generalization to argue for the originality of Ukrainian cinematography and its place in modern culture-creating processes. The scientific novelty of the study is that it describes the work of film directors whose films were created as international projects.